The Comparative Photosynthetic Responses of Pinus caribaea var. caribaea and Pinus tropicalis, from Western Cuba - García-Quintana,Yudel (2020)
Abstract This study aimed to evaluate the photosynthetic responses of Pinus caribaea Morelet var. caribaea Barret & Golfari and Pinus tropicalis Morelet in the ecological conditions of Pinar del Río, Cuba. Data were collected in March 2015 using an open system IRGA-porometer LI-6400. The response of both species was measured by increasing concentrations of carbon dioxide and photosynthetically active radiation. Results indicated that under the same environmental conditions, P. caribaea var. caribaea is more productive than P. tropicalis, since P. caribaea var. caribaea, showed higher values of net CO2 assimilation and reaching the CO2 compensation point at 77 μmol mol-1, against the 113 μmol mol-1 registered by P. tropicalis. The species P. caribaea var. caribaea reached light saturation at lower values than P. tropicalis, and showed greater efficiency for the carboxylation of Rubisco. The results indicated that both species perform C3 photosynthetic mechanism.